Cholecystitis and Choledocholithiasis in Infant: Case Report of Surgical Innovation in Paediatrics - Teles, Ariana (2019)
The incidence of cholelithiasis in paediatric age is increasing. However, the guidelines concerning the diagnostic approach and treatment are not well established and are controversial. The authors report a rare diagnosis of calculous cholecystitis and choledocholithiasis in a premature infant that attended the emergency room for persistent vomiting, diarrhoea and abdominal swelling. At this age, the clinical presentation is unspecific, the diagnosis is not obvious and the treatment is not well documented. A detailed anamnesis and the combination of several predisposing risk factors must alert the physician to the diagnosis. After an unsuccessful attempt with conservative treatment, the decision was made to try a complex surgical procedure, with diagnostic and therapeutic purposes. So far, this procedure, at this age group, has not yet been reported in the literature. Accordingly, this makes this case unique and strengthens its use as an innovative approach that achieved therapeutic success.